The plain language guide to the World Summit on Sustainable Development - Strachan, Janet R. (Earthscan, 2005)
"The Plain Language Guide to the World Summit on Sustainable Development aims to provide a quick way in to the JPOI to help promote genuine public understanding of the agreement and practical action on the commitments. It is a resource book for those working in community groups, business, local government, central government departments, regional institutions and the international community."--Jacket